Visualizing current-dependent morphology and distribution of discharge products in sodium-oxygen battery cathodes - Schröder, Daniel; Bender, Conrad L.; Osenberg, Markus; Hilger, André; Manke, Ingo; Janek, Jürgen; Justus Liebig University Giessen (My University, 2016)
Synchrotron X-ray tomography and scanning electron microscopy were applied to elucidate the spatial distribution of discharge product (NaO2) in the carbon cathode of sodium-oxygen batteries. Various batteries were discharged galvanostatically and their cathodes were analyzed. We observe a particle density gradient along the cathode that scales with the current density applied. Besides, we show that the particle size and shape of discharge product strongly depend on current density, and on whether the particles are deposited close to the oxygen reservoir or near the separator. We correlate our findings to transport limitations for the supplied oxygen and gain crucial information for optimal operation of sodium-oxygen batteries. Our findings imply that for low current densities pore clogging might occur, and that for elevated current densities small high surface area particles with limited electric conductivity form; both phenomena can decrease the available discharge and charge capacity significantly.
Keywords: ddc:540